MASS CUSTOMIZATION IN THE FASHION INDUSTRY - N. Barkova (Вестник университета)
Customization according to many scientists is individualization of the relations of the producer with the consumer. In recent years many companies working in various branches of economy began to apply it actively. The prerequisites for its using in the fashion industry have also ripened. Among them it is possible to distinguish strengthening of the competition between the companies by owners of brands, growth of requirements of buyers, high volatility of demand in this sector of economy from such prerequisites. The mass customization, satisfying individual preferences of clients, using the flexible systems of production and logistics, allows the companies of the industry of fashion to get rid of excessive stocks of the finished products tending to become outdated quickly and, above all allows to make production more attractive to consumers.